Telaah Kompetensi Guru Di Era Digital Dalam Memenuhi Tuntutan Pendidikan Abad Ke-21 - Khodijah, Siti (Institut Agama Islam Negeri (IAIN) Manado, 2018)
Abstaract., The 21st century is echoed as a century of knowledge-based society. Teachers as future human resource cadres are required to be total in carrying out their professional duties. Entering the era of digital technology revolution where experiencing various forms of change and shifting point of view, teacher competencies need to be questioned, first, are the core competencies of teachers outlined in competencies based on education levels and based on these subjects already representing the direction of education in the 21st century ?, second, how teacher readiness to welcome learning in this digital era? This literature review shows that teacher competence can be said to have represented the direction of education in the 21st century but still needs encouragement and stabilization of direction, while teacher readiness can be said to need further research for data accuracy. Keyword: teacher, teacher competence, digital era, education, 21st century Abstrak., Abad ke-21 digaungkan sebagai abad masyarakat berbasis pengetahuan. Guru sebagai sosok pengkader sumber daya manusia masa depan dituntut untuk total dalam menajalankan tugas keprofesiannya. Memasuki era revolusi teknologi digital yang mana mengalami berbagai bentuk perubahan maupun pergeseran sudut pandang maka kompetensi guru perlu dipertanyakan, pertama, apakah kompetensi inti guru yang dijabarkan dalam kompetensi berdasarkan jenjang pendidikan dan berdasarkan mata pelajaran tersebut sudah mewakili arah pendidikan Abad ke-21?,kedua, bagaimana kesiapan guru dalam menyambut pembelajaran di era digital ini?. kajian literatur ini menunjukkan bahwa kompetensi guru dapat dikatakan sudah mewakili arah pendidikan Abad ke-21 namun tetap saja perlu dorongan dan pemantapan arah, sedangkan kesiapan guru dapat dikatakan perlu penelitian lebih lanjut untuk akurasi data. Kata kuci:guru, kompetensi guru, era digital, pendidikan, Abad ke-21